ENTREPRENEURIAL FAILURE AND RESILIENCE: A CONTINUOUS INTERPLAY BETWEEN RIGIDITY AND FLEXIBILITY - Alberto Borbolla-Albores; Pavel Reyes-Mercado (Jurnal Manajemen dan Kewirausahaan, 2022)
Resilience studies are increasingly relevant to understand business processes. This study aimed to explore how entrepreneurs in Mexico recovered from situations of business failure. Which key factors did move entrepreneurs to move forward with their ventures rather than desisting after a failure event? Through a qualitative study that utilized focus groups with entrepreneurs that had faced entrepreneurial failure, discourses, and representations around the failure experience were analyzed. Findings suggested that entrepreneurs lied in a continuum between resilience and resistance, depending on their access assets such as entrepreneurial networks, ecosystems, and pool of knowledge as antecedents of resistance and resilience. The study shed light in the understanding of the role communities surrounding entrepreneurs played in their trajectory, failure, and eventual recovery.